Investigation of a Contaminated, Nationally Distributed, Organ Transplant Preservation Solution — United States, 2016–2017. (4th October 2017) - Stuckey, Matthew; Novosad, Shannon; Wilde, Nancy; Annambhotla, Pallavi; Basavaraju, Sridhar; Moulton-Meissner, Heather; Seiber, Kathy; Perz, Joseph; Quinlisk, Patricia; Garvey, Ann; Conrad, Suzanne; Fewell, Sarah; et al.
Abstract: Background: In December 2016, bacterial contamination of an organ preservation solution (OPS) was reported by Transplant Center A in Iowa. Annually, >20, 000 abdominal organs are transplanted in the United States; OPS is used for organ storage. We investigated the scope of OPS contamination and its association with adverse events in patients. Methods: We assessed infection control practices related to OPS at Transplant Centers A and B in Iowa and the local organ procurement organization (OPO). We issued national notifications about OPS contamination and requested transplant centers to report product-related concerns or potential patient harm. Among transplant recipients at Center A, we compared adverse events (fever, bacteremia, surgical site infection, peritonitis, or pyelonephritis within 14 days of transplantation) during October–December 2015 with October–December 2016, the presumed window of exposure to contaminated OPS. Isolates from OPS were characterized. Results: No infection control deficiencies were identified at Transplant Centers A, B, or the OPO. In January 2017, contaminated OPS from the same manufacturer was reported by Transplant Center C in Texas. Nationally, there were no reports of patient harm definitively linked to OPS. Post-transplant adverse events at Center A did not increase between fourth quarter 2015 (5/12 [42%]) and 2016 (2/15 [13%]). Organisms recovered from OPS included Pantoea agglomerans and Enterococcus gallinarum (Center A) and Pseudomonas koreensis (Center C). Five Pantoea isolates from ≥3 opened OPS bags were indistinguishable by pulsed-field gel electrophoresis. The OPS distributor issued recalls and suspended production. The US Food and Drug Administration identified deficiencies in current good manufacturing practices at manufacturing and distribution facilities, including inadequate validation of OPS sterility. Conclusion: Bacterial contamination of a nationally distributed product was identified by astute clinicians. The investigation found no illnesses were directly linked to the product. Prompt reporting of concerns about potentially contaminated healthcare products, which might put patients at risk, is critical for swift public health action. Disclosures: All authors: No reported disclosures.